Evaluating User Continuance Intentions for QRIS Mobile Payments Services Using Information System Success Model and Expectation Confirmation Model - Wiyan Herra Herviana; Zaenal Abidin (Journal of Advances in Information Systems and Technology, 2024)
QRIS services on mobile payment applications are one of Indonesia's most popular payment methods, and they allow transactions by scanning or displaying the QR code. This enables mobile-based payments to be easy and flexible anywhere and anytime. As it grows and benefits, some obstacles exist regarding users' desire to continue using it. Some users decided to stop using the QRIS service for mobile payments due to indications of potential risks associated with the service. This research aims to find out what variables support or influence the intention to continue using QRIS services for mobile payments using quantitative methods and the information system success model (ISSM) and expectation confirmation model (ECM) frameworks by adding perceived risk and trust variables. The data collection technique used in this study was a questionnaires survey using Google Forms and applying purposive sampling techniques. The survey targeted QRIS service users aged 17 to 65 who experienced transactions using mobile payments (e-wallets and mobile banking). The data was collected from 513 respondents and analyzed using the partial least squares structural equation model (PLS-SEM) by Smart-PLS 4 software tools. The findings were that 10 hypotheses were declared accepted and five hypotheses were rejected. Based on the accepted hypothesis, research shows that satisfaction and trust influence the intention to continue using QRIS services for mobile payments. Satisfaction is a key factor that supports or influences a user's decision to continue using or utilizing QRIS payment services. The findings of this research can be an essential consideration for developers and companies providing QRIS services in mobile payments.